Assessing Soil Nutrient and Biomass Contributions to Peatland Formation - M. Edi Armanto; Elisa Wildayana; Momon Sodik Imanudin (PLANTA TROPIKA, 2025)
Peat formation is a key factor in carbon sequestration in  Peat Swamp Forest (PSF). The study aims to analyze alternative pathways for peat formation based on soil nutrient availability and dried biomass accumulation. A randomized complete block design was used with two treatment factors across three blocks: (A) sampling plots representing land covers and (B) dried biomass levels. Data were analyzed using two-way ANOVA and Tukey Honestly Significant Difference (HSD) test at a 5 % significance level. Results showed a high supply of dried below-ground biomass did not correspond to increased rooting litter production under high soil nutrient conditions. Instead, most of the biomass was transported upwards into above-ground biomass. All land cover types generated above-ground biomass with significant differences in peat formation potential across all measured parameters. Peat formation was strongly influenced by land cover type (e.g., peat forest), environmental factors, seed bank composition, and species competition. Restoration strategies, including revegetation, rewetting, and revitalization, are crucial to promoting the establishment of peat-forming species. This research provides valuable insights for enhancing  PSF restoration efforts and facilitating recovery toward a near-natural condition.